2023
DOI: 10.3390/photonics10040451
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of 12.5 Mslot/s 32-PPM Underwater Wireless Optical Communication System with 0.34 Photons/Bit Receiver Sensitivity

Abstract: High-capacity, long-distance underwater wireless optical communication (UWOC) technology is an important component in building fast, flexible underwater sensing networks. Underwater communication with light as a carrier has a large communication capacity, but channel loss induced by light attenuation and scattering largely limits the underwater wireless optical communication distance. To improve the communication distance, a low-power 450 nm blue continuous wave (CW) laser diode (LD)-based UWOC system was prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It is vital to prioritize modulation schemes with high transmission rates or high transmission efficiency while assuring dependability [ 21 , 22 , 23 ]. Most UWOC studies have been carried out utilizing PPM, or on-off keying (OOK), as the modulation format in the water channel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is vital to prioritize modulation schemes with high transmission rates or high transmission efficiency while assuring dependability [ 21 , 22 , 23 ]. Most UWOC studies have been carried out utilizing PPM, or on-off keying (OOK), as the modulation format in the water channel.…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Yan et al demonstrated an 84 m/1 Mbps UWOC system using 256 PPM [ 20 ]. In 2023, Han et al demonstrated an underwater wireless optical communication system based on 32 PPM modulation, achieving a communication distance of 35.64 m and a communication rate of 1.9 Mbps [ 21 ]. As such, PPM has become the modulation format selected by most researchers.…”
Section: Introductionmentioning
confidence: 99%